Biancaneve e sette anni - «Qualcosa da prendere sul serio»: un dibattito nel 1979 - Stocco, Ester (Il sogno della farfalla, 2023)
Biancaneve e sette anni - «Qualcosa da prendere sul serio»: un dibattito nel 1979